The Smallest Bipartite Intrinsically Knotted Graph - Johnson, Brenda; Li, Shizhe (The PUMP Journal of Undergraduate Research, 2024)
We use the restoring method of Kim, Mattman, and Oh to prove that the Heawood graph is the only bipartite graph with 21 edges that is intrinsically knotted.